Solve the equation √x+3=x+1

x=

1 answer

Squaring both sides of the equation, we get (√x+3)^2=(x+1)^2. Expanding both sides, we have x+3+6√x=x^2+2x+1. Rearranging the terms and simplifying, we get 2x-x^2=2-6√x. Moving all terms to one side, we have x^2-2x+2-2=6√x. Simplifying further, we get x^2-2x=6√x-2. Squaring both sides again, we get x^4-4x^3+4x^2=36x-24√x+4. Rearranging and simplifying, we get x^4-4x^3+4x^2-36x+24√x-4=0. At this point, it is not possible to solve for x algebraically, so we would need to use numerical methods or a graphing calculator to find the approximate value of x.